Enhancing Transformative Competencies through the Internalization of Religious Moderation: A Vision for Islamic Boarding School's Educational Framework in 2030 - Junaedi Junaedi; M. Zainuddin; Muhammad Walid; Mamluatul Hasanah; Ahmad Barizi (AL-ISHLAH: Jurnal Pendidikan, 2024)
Extremism, radicalism, hate speech, and even the rupture of inter-religious ties, are problems facing the Indonesian nation today. Al-Hikam as one of the boarding schools able to survive in those problems, by encouraging religious moderation. This study aims to explore the process of internalizing the value of religious moderation in Al-Hikam Islamic boarding schools and analyze the realization of transformative competencies in the process. An instrumental case study design was chosen for this research. Observation and in-depth interviews were conducted to obtain data. The results showed that there were 3 models of value transformation, verbal, symbolic, and written. The methods of imparting values are carried out in two ways, namely providing standardized sources of accurate information and structured practices through pesantren programs and activities. The internalization process is formed through joint service activities involving various elements of the moderation agency. This study arrived at the theoretical finding that maximizing the function of co-agency in pesantren consisting of the Kyai board, teachers, peer colleagues, and santri guardians at the transaction stage, is effectively facilitates the internalization of values by the agents (santri) of religious moderation obtained at the transformation stage into an inherent identity, namely moderate humans. This achieved identity also brings students to achieve transformative competencies: creating new values, reconciling tensions and dilemmas, and taking responsibility.